Mathematical disquisitions : the booklet of theses immortalized by Galileo - Graney, Christopher M., 1966- (University of Notre Dame Press, 2017)
Johann Georg Locher wrote Disquisitiones Mathematicae (Mathematical Disquisitions) in 1614, about astronomy and the sun. Galileo replied, through Dialogue Concerning the Two Chief World Systems, Ptolemaic and Copernican, in 1632.